Dividendos: análisis de las reformas tributarias en el Ecuador y la incidencia sobre la recaudación, 2008 al 2018 - Camacho Torres, Oscar Iván (2021)
Nowadays, dividend taxing represents a central interest issue on the part of government tax administration units worldwide, due to the linkage between the profits generated by the companies and the dividend income received by shareholders. This research seeks to descriptively compare the regulations related to dividends and their evolutionary tax treatment during the period under study. Dividends are considered as part of income taxed within the global income of natural persons, modified not only to ensure greater tax pressure on capital income by the tax administration, but also to increase more resources to the state. The methodological approach is descriptive-comparative, using descriptive statistics as an analysis tool. The data was obtained from the Internal Revenue Service, regarding forms 102, considering mainly the Income Tax of natural persons, income received from dividends, withholdings and tax credits for dividends, with an additional variable that corresponds to dividend income. In the same way, an analysis of a documentary type is carried out from the review of the legal regulations generated and reformed during the period under study. It is shown that, income taxed on dividends of natural persons and their tax credit for this same concept, more than benefiting the state, they reduce the revenue flow of tax administration.